Risk management in inpatient units in the Czech Republic from the point of view of nurses in leadership positions - Prokešová, Radka; Brabcová, Iva; Pokojová, Radka; Bártlová, Sylva (Neuro-endocrinology letters, 2016)
OBJECTIVES: The goal of this study was to assess specific features of risk management from the point of view of nurses in leadership positions in inpatient units in Czech hospitals. METHODS: The study was performed using a quantitative research strategy, i.e., a questionnaire. The data sample was analyzed using SPSS v. 23.0. Pearson's chi-square and analysis of adjusted residues were used for identifying the existence associations of nominal and/or ordinal quantities. 315 nurses in leadership positions working in inpatient units of Czech hospitals were included in the sample. The sample was created using random selection by means of quotas. RESULTS: Based on the study results, statistically significant relations between the respondents' education and the utilization of methods to identify risks were identified. Furthermore, statistically significant relationships were found between a nurse's functional role within the system and regular analysis and evaluation of risks and between the type of the healthcare facility and the degree of patient involvement in risk management. CONCLUSION: The study found statistically significant correlations that can be used to increase the effectiveness of risk management in inpatient units of Czech hospitals. From this perspective, the fact that patient involvement in risk management was only reported by 37.8% of respondents seems to be the most notable problem.
Keywords: Hospitals; Česká republika; kvalitativní výzkum; Inpatients; Leadership; Risk Management; Czech Republic; řízení rizik; hospitalizovaní pacienti; Nurse's Role; Nursing Staff, Hospital; lidé; Qualitative Research; nemocnice; role ošetřovatelky; personál sesterský nemocniční; vůdcovství; Humans